The Absence of Generosity and Obedience to Authority: Judgments of Teachers and Students From Kindergarten1 - Kawashima, Rosana Akemi [UNESP]; Martins, Raul Aragão [UNESP] (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, 2015)
Preschool Education can provide conditions for the construction of moral values in children. This study’s objective was to investigate the judgment of teachers and students in Primary Education regarding the virtue of generosity and whether, in this judgment, it is valued more than obedience to authority. Interviews were held with 26 teachers and 90 children from four municipal schools, using a stimulus-story about an activity using modeling clay. The results indicated that, for the majority of participants, the attitude of the teacher in the stimulus-story, in not helping the child and demanding obedience in first place, is wrong. In relation to the reasons, for the majority of the teachers, the lack of help is justified because the activity with the modeling clay should be free, prioritizing the child’s wishes. For the majority of the children, however, the teachers’ lack of help is felt as failure to attribute postive value. Furthermore, it was observed that the strength of the virtue of generosity among the participants in this study is weak.

La Educación Infantil puede proporcionar condiciones para la construcción de los valores morales en los niños. La finalidad de este estudio fue investigar los juicios de los profesores y niños de la Educación Infantil respecto a la virtud de la generosidad y si esta virtud es más valorada que la obediencia. Fueron entrevistados 26 profesores y 90 niños de cuatro escuelas municipales, les presentando una historia-estímulo. Los resultados indican que, para la mayoría de los participantes, la actitud de la profesora es equivocada, además de exigir obediencia primero. Respecto a las justificativas, para la mayoría de las profesoras, la falta de ayuda se justifica porque la actividad debe ser libre, priorizando la voluntad del niño. Sin embargo, para la mayoría de los niños, la falta de ayuda por parte del profesor se percibe como falta de atribución de valor positivo. La fuerza de la virtud generosidad es débil entre los participantes de esta investigación.

A Educação Infantil pode proporcionar condições para a construção dos valores morais nas crianças. O objetivo deste estudo foi investigar os juízos de professores e alunos da Educação Infantil em relação à virtude generosidade e se nesse juízo ela é mais valorizada que a obediência à autoridade. Foram entrevistados 26 professores e 90 crianças de quatro escolas municipais, utilizando-se uma estória-estímulo sobre uma atividade com massa de modelar. Os resultados indicaram que, para a maioria dos participantes, é errada a atitude da professora da estória-estímulo em não ajudar a criança e exigir obediência primeiramente. Quanto às justificativas, para a maioria das professoras, a falta de ajuda se justifica porque a atividade de massa de modelar deve ser livre, priorizando a vontade da criança. No entanto, para a maioria das crianças, a falta de ajuda da professora é sentida como falta de atribuição de valor positivo. Além disso, foi constatado que é fraca a força da virtude generosidade entre os participantes desta pesquisa.
La Ausencia de Generosidad y Obediencia a la Autoridad: Juicios de los Profesores y los Niños de Educación Infantil
Ausência de Generosidade e Obediência à Autoridade: Juízos de Professores e Crianças da Educação Infantil
Keywords: generosity; obedience; preschool education; moral development; pre-school educators; generosidade; obediência; educação infantil; desenvolvimento moral; educadores infantis